Model jakości usług ubezpieczeniowych. Metodologia badań - próba syntezy - Garczarczyk, Józef (Model of Insurance Service Quality. Research Methodology - Synthesis Trial, 2008)
The article presented an attempt to application of different statistic-econometric methods (regression/correlation analysis, factor analysis) to create multidimensional models of insurance service quality. This allowed to capture relations among service quality attributes in subsequent phases of creating the quality protection system in an insurance company. The analyses carried out in the paper proved the adequacy of the used methods in quality measurement and allowed to present the subject from different points of view.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 69-79